2015
DOI: 10.1007/s00415-015-7806-4
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous value of anti-ganglioside IgM autoantibodies in Guillain-Barré syndrome and its variants

Abstract: Anti-ganglioside autoantibodies of the IgG type are detected in a half of patients with Guillain-Barré syndrome (GBS), and their detection strongly supports the diagnosis of GBS. In contrast, anti-ganglioside IgM antibodies are also often detected in GBS patients, but it remains unclear whether IgM antibodies indicate a diagnosis of GBS. We identified four GBS patients (3.3%) who tested positive for IgM antibodies but negative for IgG antibodies among 122 patients with GBS and its variants. These four patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…In this study, IgM antibodies were more common than IgG antibodies in the CIDP patients, and similar frequencies of these 2 antibody types were observed in the GBS patients, in contrast to findings from another country (Table ) . IgG anti‐ganglioside antibodies were detected in half of the GBS patients in this study, and IgG detection is strong evidence for a diagnosis of GBS . Another study of Chinese patients reported that IgG anti‐GM1 antibodies against gangliosides were more common in GBS patients, whereas the frequencies of IgG antibodies against other gangliosides did not differ significantly .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, IgM antibodies were more common than IgG antibodies in the CIDP patients, and similar frequencies of these 2 antibody types were observed in the GBS patients, in contrast to findings from another country (Table ) . IgG anti‐ganglioside antibodies were detected in half of the GBS patients in this study, and IgG detection is strong evidence for a diagnosis of GBS . Another study of Chinese patients reported that IgG anti‐GM1 antibodies against gangliosides were more common in GBS patients, whereas the frequencies of IgG antibodies against other gangliosides did not differ significantly .…”
Section: Discussionsupporting
confidence: 78%
“…Although we found that IgM antibodies were more common than IgG antibodies in our population, there were no significant differences in IgM positivity between the AIDP and AMAN patients. Similarly, a recent study showed that IgM anti‐ganglioside antibodies are considerably limited compared with IgG antibodies for determining the particular disease present . Kuwahara et al .…”
Section: Discussionmentioning
confidence: 98%
“…Serum IgM and IgG antibodies against isolated gangliosides (GM2, GM1, GD1a, GalNAc-GD1a, GD1b, GT1a, GT1b, or GQ1b; 10 pmol/well) and ganglioside complexes (GM1/GD1a and GM1/GT1a) were measured by enzyme-linked immunosorbent assay (ELISA) as described elsewhere [ 9 ]. IgG subclasses of anti-GQ1b and anti-GT1a antibodies were examined as reported previously [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…79 In particular, IgG AGAs are found in more than half of GBS patients and are strongly indicative of the disease, while the role of IgM is still not clear. 80 GBS a is the most common cause of a flaccid pararalysis worldwide. It is considered to be a postinfectious, inflammatory, peripheral neuropathy.…”
Section: Gq1bmentioning
confidence: 99%